Farmer Perceptions and Determinants of Sustainable Agriculture at the Farm Level: A Case Study of Musanze, Kirehe and Gisagara Districts of Rwanda / Shakiru Muhamadi ; Supervisor İsmet Boz - Muhamadi, Shakiru (Ondokuz Mayıs Üniversitesi, Fen Bilimleri Enstitüsü, 2016)
…
Tez (yüksek lisans) -- Ondokuz Mayıs Üniversitesi, 2016
Libra Kayıt No: 92105
Keywords: Tarım; Tarım -- Afrika; TEZ YÜK LİS M952f 2016